Literature Review: Effectiveness of Roxadustat Administration in the Management of Anemia in Patients with Chronic Kidney Disease - Anak Agung Istri Dwi Sarasmita Dewi; Ketut Indra Purnomo; Made Budiawan (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Chronic kidney disease (CKD) is a global health burden with high morbidity and mortality. Anemia is a common complication that worsens quality of life, increases cardiovascular risk, and reduces survival. Roxadustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI), represents a novel therapy by stimulating endogenous erythropoietin, lowering hepcidin, and improving iron metabolism. Objective: To evaluate the effectiveness and safety of roxadustat in managing anemia among CKD patients. Methods: A literature review was performed through PubMed, Google Scholar, and ScienceDirect. Six studies, including randomized controlled trials, retrospective cohorts, and real-world registry data, were analyzed. Results: Roxadustat consistently increased hemoglobin and maintained it within therapeutic targets in both dialysis and non-dialysis patients. It improved iron utilization, reduced intravenous iron needs, and showed favorable lipid effects. The safety profile was generally comparable to erythropoiesis-stimulating agents, with no significant increase in cardiovascular or infectious adverse events. Conclusion: Evidence indicates that roxadustat is an effective, safe, and practical treatment for anemia in CKD. Its ability to optimize hemoglobin control, enhance iron metabolism, and maintain safety supports its potential as an alternative to conventional therapy.